Justification within Recapitulation: Irenaeus in Ecumenical Dialogue - Boersma, Hans (International journal of systematic theology, 2020)
Justification has a relatively minor place in Irenaeus's thought. He discusses it particularly in his polemics against Gnostic approaches to the Scriptures and to the law. Justification typically serves for Irenaeus within a broader, participatory framework of salvation. When we take these aspects into account, unexpected ecumenical possibilities open up between Orthodox, Catholics and Protestants. One of the most important lessons from Irenaeus's discussion on justification, therefore, is that justification should not be treated as an insulated doctrine. Instead, it is an aspect of participation in Christ's recapitulation and as such serves to uphold and strengthen our deifying union with God in Christ.